PERANCANGAN APLIKASI KEAMANAN PESAN TEKS DENGAN MENGGUNAKAN ALGORITMA TRIPLE DES - Siregar, Nurmarlina (STMIK KAPUTAMA, 2019)
Triple DES (Triple Data Encryption Standard) is one of the symmetrical algorithms on cryptography that is used to secure data in the form of text messages by encoding text messages. The process carried out in encoding the data, namely the encryption process and the decryption process. The triple DES algorithm is an algorithm for the development of the DES (Data Encryption Standard) algorithm. The difference between DES and triple DES lies in the length of the key used. In DES it uses one key that is 56-bit long, while triple DES uses three keys that are 168-bits in length (each of which is 56 bits long). In triple DES, the three keys used can be mutually independent (K1, K2 and K3) or only two keys are mutually independent and one other key is the same as the first key (K1, K2 and K3 = K1). Because the level of confidentiality of the DES algorithm lies in the length of the key used, the use of the triple DES algorithm is considered safer than the DES algorithm. To facilitate the use of the triple DES algorithm, a triple DES algorithm program was created with computer software tools, namely Microsoft Visual Studio 2008 which can encrypt and decrypt text messages.